AMS radiocarbon dates from Baltic Sea sediment core EMB201/13-4 - Daniela J M Müller; Ina Neugebauer; Rebecca J Kearney; Markus J Schwab; Oona Appelt; Markus Czymzik; Jérôme Kaiser; Helge Wolfgang Arz; Achim Brauer (PANGAEA, 2025)
Four radiocarbon samples were taken from the same depth intervals as the identified 1-cm thick cryptotephra isochrons in core EMB201/13-4. The four accelerator mass spectrometer (AMS) 14C ages were obtained from the humic acid fraction of bulk organic matter samples and measured in the Beta Analytic Radiocarbon Dating Laboratory. Uncalibrated and calibrated radiocarbon ages are provided. For comparison with previous studies, calibration followed the published methodology in the Baltic Sea (e.g. Moros et al. 2020) of subtracting the global-average marine reservoir age of 400 years (from IntCal13) before applying OxCal v4.4 (Ramsey, 2009) and IntCal20 (Reimer et al., 2020). Calibrated ages are given as median and with both, 1σ and 2σ uncertainties.
In: Müller, DJM et al. (2025): Major element geochemistry of tephra glass shards and age model construction in Baltic Sea sediment cores EMB201/13-4 and POS507/29-2 [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.984844 (DOI registration in progress)